Sagata sebagai Ciri Khas Tradisi Lisan Masyarakat Lampung Saibatin - Delvina Maulhy Azahra Hulu; Dwi Agustiana Putri; Rahmat Prayogi; Bambang Riadi (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Through this research, it is hoped that it will be possible to reveal how sagata has become an integral part of the life of the Saibatin community, as well as how this oral literature reflects the worldview, value system and social norms that have developed in this community. With a deeper understanding of sagata, this research also aims to highlight the importance of efforts to preserve oral traditions amidst increasingly rapid global changes. This research uses a descriptive qualitative research method using library research, which involves collecting coverage and research based on literature, which involves collecting information and research through library references, such as books, scientific journals and other reliable sources related to Sagata as an oral tradition. This oral tradition includes several cultural aspects including folklore, folk tales, traditional songs, and other oral literature. Sagat can also contain stories about the origins of a place, heroic stories, myths or history. Oral tradition is a step that needs to be preserved and passed on the knowledge, cultural norms and identity of the Lampung people.